"Take me to the river": mapping global flows from crayons to connections - Kirshner, Jean Denison, author; Kamberelis, George, advisor; Jennings, Louise, advisor; Anderson, Sharon, committee member; Vigil, Patricia, committee member (Colorado State University. Libraries, 2019)
In this dissertation I studied an ongoing professional development project that involved educators from Belize and the United States. In the end I argue that sustainable change within transnational and transcultural professional development activities and research projects is most effective when it involves Freirean-like dialogue, sharing life stories and sharing lifeworlds. Using a Participatory Action Research (PAR) approach, I used interviews, focus groups, personal communications, and field notes of professional development activities to document the life stories, shared dialogue, and lived worlds of my colleagues in Belize. Using a basic thematic analysis approach, my Belizean colleagues and I distilled themes from the data to more deeply understand my colleagues' lives and perspectives on literacy and education. Embracing a fully collaborative (or participatory) research approach, I chose to represent our collective work as a narrative. Several key themes emerged from analyses: the effects of colonialism and postcolonialism on the entire enterprise, the exigencies of becoming a teacher in Belize, the effects of engaging in Freirean dialogue, sharing life stories, and sharing life worlds on teachers' identities and practices. First, I describe the context of colonialism/postcolonialism in which this work was embedded. Then I chronicle the early years of Belize Education Project's work. I begin by describing the origins of the Belize Education Project (BEP) and its focus on providing material resources and "best practice" teaching strategies to teachers in Belize. Importantly, I describe a watershed moment in which I realized that something more—something more human and more humanizing—was needed for the project to flourish. After that, I map the exigencies of becoming and being a teacher in Belize, a trajectory closely linked to forces of colonialism/postcolonialism. I also explain how intentionally enacting Freirean-like dialogue, sharing life stories, and sharing lifeworlds, led to key changes in the professional identities and practices of all BEP participants, my Belizean colleagues as well as members of Belize Education Project in the United States. Finally, I discuss the effects of changing relationships, identities, and practices on pedagogy and student outcomes in Belizean classrooms. I conclude by discussing the relevance of my findings for transnational and transcultural professional development work and global educational stewardship.
Take me to the river: mapping global flows from crayons to connections
Keywords: professional development; cross cultural